The Oxford handbook of Roman sculpture - Friedland, Elise A.; Grunow Sobocinski, Melanie; Gazda, Elaine K. ([Oxford handbook], 2015)
Collecting in Premodern Europe / Elizabeth Bartman -- Conservation and Restoration / Jerry Podany -- Collecting in Early America / Hima Mallampati Gleason -- Current Trends in Museum Display / Jessica Powers -- Three-Dimensional Scanning and Modeling / Bernard Frischer -- Marble Quarries: Ancient Imperial Administration and Modern Scientific Analyses / Patrizio Pensabene and Eleonora Gasparini Translated by Massimo Carlucci -- Marble Carving Techniques, Workshops, and Artisans / Amanda Claridge -- Reuse and Recarving: Technical Evidence / Eric R. Varner -- Bronzes / Carl C. Mattusch -- Terracottas / Adi Erlich -- Polychromy / Mark B. Abbe -- Transport and Distribution / Ben Russell -- Style: Applications and Limitations / Mark D. Fullerton -- Etruscan Connections / Nancy T. De Grummond -- "Idealplastik" and the Relationship between Greek and Roman Sculpture / Anna Anguissola -- Portraiture / Susan Wood -- Monumental Reliefs / Melanie Grunow Sobocinski and Elizatbeth Wolfram Thill -- Archaism and Eclecticism / Lori-Ann Touchette -- Egyptian-Style Monuments / Molly Swetnam-Burland -- Late Antique Sculpture / Christian Witschel -- Architectural Settings / Brenda Longfellow -- Religious Dedications / Matthew M. McCarty -- Domestic Displays / Elaine K. Gazda -- Funerary Monuments / Bjorn C. Ewald -- Epigraphy and Patronage / Steven L. Tuck -- Imperial Messages / Barbara Kellum -- Non-Elite Patronage / Lauren Hackworth Petersen -- Gender / Eve D'Ambra and Francesca Tronchin -- Northern Gaul, Germany, and Britain / Kimberly Cassibry -- Hispaniae and Narbonensis / Alicia Jimenez and Isabela Roda -- North Africa / Francois Barrate and Nathalie De Chaisemartin -- Greece / Mary C. Sturgeon -- Asia Minor / Diana Y. Ng -- Egypt / Christina Riggs -- Near East / Thomas Maria Weber -- Aesthetics and Latin Literary Reception / Michael Squire -- Reception Theory / Jennifer Trimble -- Ancient Analogs of Museums / Josephine Shaya -- Images of Statues in Other Media / Eric M. Moormann -- Human Interactions with Statues / Ellen E. Perry -- Iconoclasm / Troels Myrup Kristensen